Interphase evolution in polymer films by confocal Raman microspectroscopy - Tomba, Juan Pablo (2006)
Liquid-glassy polymer diffusion is an important topic in polymer physics, with several mechanistic aspects that still remain unclear. Here we describe the use of confocal Raman microspectroscopy (CRM) to study directly several features of interphase evolution in a system of this type. The interphase studied was generated by contact between liquid polystyrene (PS) and glassy polyphenylene oxide (PPO). Interphase evolution on thin films made from these polymers was followed by depth profiling in combination with immersion optics. We also applied regularized deconvolution to improve the spatial resolution of the measurements. With the help of these techniques, we examined interphase PPO concentration profiles and kinetics of interphase evolution in the range 120-180°C, well below the glass transition temperature of the PPO-based films (185°C). Overall, the experiment captures the most important features needed to discern the mechanistic factors that control this process. In this sense, confocal Raman microspectroscopy emerges as one of the best experimental techniques for the study of diffusion kinetics in this type of system.